Crystal structure of the capsular polysaccharide‐synthesis enzyme CapG from Staphylococcus aureus. Issue 11 (14th October 2022) - Tien, Ni; Ho, Chien-Yi; Lai, Shu-Jung; Lin, Yu-Chuan; Yang, Chia-Shin; Wang, Yu-Chuan; Huang, Wei-Chien; Chen, Yeh; Chang, Jui-Jen
Abstract : The crystal structure of CapG from Staphylococcus aureus ( Sa CapG) forms a homohexamer, in contrast to the dimeric or tetrameric assembly of its bacterial homologues. The conformational flexibility of α2, the α2–α3 loop and α10 of Sa CapG probably facilitates the binding of substrates and/or the release of products. Abstract : Bacterial capsular polysaccharides provide protection against environmental stress and immune evasion from the host immune system, and are therefore considered to be attractive therapeutic targets for the development of anti‐infectious reagents. Here, we focused on CapG, one of the key enzymes in the synthesis pathway of capsular polysaccharides type 5 (CP5) from the opportunistic pathogen Staphylococcus aureus . Sa CapG catalyses the 2‐epimerization of UDP‐ N ‐acetyl‐d ‐talosamine (UDP‐TalNAc) to UDP‐ N ‐acetyl‐d ‐fucosamine (UDP‐FucNAc), which is one of the nucleotide‐activated precursors for the synthesis of the trisaccharide repeating units of CP5. Here, the cloning, expression and purification of recombinant Sa CapG are reported. After extensive efforts, single crystals of Sa CapG were successfully obtained which belonged to space group C 2 and exhibited unit‐cell parameters a = 302.91, b  = 84.34, c = 145.09 Å, β = 110.65°. The structure was solved by molecular replacement and was refined to 3.2 Å resolution. The asymmetric unit revealed a homohexameric assembly of Sa CapG, which was consistent with gel‐filtration analysis. Structural comparison with UDP‐ N ‐acetyl‐d ‐glucosamine 2‐epimerase from Methanocaldococcus jannaschii identified α2, the α2–α3 loop and α10 as a gate‐regulated switch controlling substrate entry and/or product release.